Colonic J-pouch versus side-to-end anastomosis for rectal cancer: a systematic review and meta-analysis of randomized controlled trials - Wang, Zheng (BMC surgery, 2021)
Background This study aims to compare colonic J-pouch and side-to-end anastomosis for rectal cancer in terms of surgical and bowel functional outcomes and quality of life (QoL). Methods A systematic literature search was performed in PubMed, Embase and Cochrane. The last search was performed on March 28, 2021. All randomized controlled trials comparing colonic J-pouch with side-to-end anastomosis for rectal cancer were enrolled. The main outcomes were bowel functional outcomes and QoL. The secondary outcomes were surgical outcomes including operative time, postoperative hospital stay, complications, and mortality. Results Nine articles incorporating 7 trials with a total of 696 patients (330 by J-pouch and 366 by side-to-end) were enrolled in this meta-analysis. The bowel functional outcomes were comparable between J-pouch and side-to-end groups in terms of stool frequency, urgency, and incomplete defecation at the short term (< 8 months), medium term (8-18 months), and long term (> 18 months) follow up evaluations. No difference was observed between groups with regards to QoL (SF-36: physical function, social function, and general health perception). Besides, surgical outcomes were also similar in two groups. Conclusion The currently limited evidence suggests that colonic J-pouch and side-to-end anastomosis are comparable in terms of bowel functional outcomes, QoL, and surgical outcomes. Surgeons may choose either of the two techniques for anastomosis. A large sample randomized controlled study comparing colonic J-pouch and side-to-end anastomosis for rectal cancer is warranted. Keywords: Rectal cancer, Colonic J-pouch anastomosis, Side-to-end anastomosis, Meta-analysis